Nilai-nilai Qur’ani Spritualitas Profetik dalam membangun Budaya Anti Korupsi - Syarifuddin Syarifuddin; Andini Febrianty Damasari; Amaruddin Amaruddin (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2021)
Islam has a strategic concept of teaching in an effort to prevent falling into acts that are prohibited by religion. In the concept of religion, it is called nahi munkar.. Included in the actions that are given a warning are the prohibition of corruption. Corruption is also referred to as an extraordinary crime in terms of its extraordinary impact on life. There are many aspects of corruption that need attention, especially in the person of Muslims. The pattern of character building through a culture of avoiding corruption needs to be built and instilled from the start. One that is relevant in the construction is the offer of the concept of Qur'anic values ​​in aspects of prophetic spirituality; shiddiq, amanah, tabligh, and fathanah. These four values ​​are very likely to be developed and socialized in the realm of the civilizing system in society, which involves institutional relationships and individual and social responsibilities. So by applying these values ​​in a policy or ethical system, it means that the Qur'an has been grounded at its practical level.